Maximally node and SRLG-disjoint path pair of min-sum cost in GMPLS networks: a lexicographic approach - Gomes, Teresa (2018)
Path protection is a fast and capacity-efficient approach for increasing the availability of end-to-end connections. However, sometimes it is not possible to obtain a fully disjoint path pair. In this case, it may be admissible to consider a path pair which is as disjoint as possible, and thus provide the best (in a certain sense) level of the single-fault protection that can be ensured using this type of approach. A shared risk link group (SRLG) is a group of links which have a common risk of failure. Two new heuristics for solving the min-sum maximally node and SRLG-disjoint path pair are presented. The relative performance of the new heuristics and also of two other previously proposed heuristics is evaluated using four different networks. Results, regarding accuracy and execution time of the studied heuristics, show that one of the new proposed algorithms can be a good compromise for use in the Generalized Multi-protocol Label Switching control plane.